Hubungan Peran Keluarga dengan Sikap dalam Upaya Pencegahan Ispa pada Anak Balita di Wilayah Kerja UPTD Puskesmas Bukit Hindu Palangka Raya - Ananda Micolla Mandau Saputra; Putria Carolina; Tomi Satalar (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Acute Respiratory Infection (ARI) is one of the diseases that frequently affects children under five years old and is a major cause of high disease rates in Indonesia. In the working area of the Bukit Hindu Health Center in Palangka Raya, cases of Acute Respiratory Infection (ARI) in toddlers tend to increase every year. This study was conducted to determine the relationship between family roles and their attitudes in preventing Acute Respiratory Infections (ARI) in children under five years old. The study aimed to determine the relationship between family roles and attitudes in preventing ARI in children under five years old within the working area of the Bukit Hindu Palangka Raya Public Health Center. This research is quantitative research with a correlational design and a cross-sectional approach. Samples were taken from 40 respondents using a purposive sampling technique. Data was collected using questionnaires and analyzed with the Spearman Rank statistical test. The research results showed that most respondents had a good family role and attitude toward preventing ARI. The results of the Spearman Rank test showed a significance value of p = <0.001 and a correlation coefficient value of 0.941*, indicating a very strong relationship between family role and attitudes in efforts to prevent ARI in toddlers. There is a significant relationship between family roles and attitudes in the effort to prevent ARI in toddlers within the working area of the Bukit Hindu Health Center Palangka Raya.